A Bathymetric and Geomagnetic Survey of the New England Seamount Chain - Walczak, J. E.; Carter, T. (The International Hydrographic Review, 2015)
During June, July, and August of 1962, the U. S. Naval Oceanographic Office assigned a survey ship, the USS Sheldrake AGS-19, to conduct a systematic bathymetric and geomagnetic survey of the New England Seamount Chain. The location of the surveyed areas is shown in figure 1. Four of the six tracks which were run between these areas and the mainland also are shown in figure 1. Data records were processed aboard ship and the information was later plotted and contoured at the Oceanographic Office.